Pengaruh Electronic Word of Mouth dan Traditional Word of Mouth Terhadap Keputusan Berkunjung dengan Kepuasan Pengunjung Sebagai variabel Mediasi di Situ Cipondoh, Kota Tangerang, Provinsi Banten - Dira Oktavia, Reno Catelya; Rachmatullah, Adam; Oktovianus, Oktovianus; Enggriani, Mimi; Maudiarti, Santi (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2024)
This research aims to determine the influence of Electronic Word of Mouth and Traditional Word of Mouth on visiting decisions through visitor satisfaction at Situ Cipondoh, Tangerang City. The background of this research is based on the importance of communication from previous visitors in influencing the behavior of new visitors. The method used is a quantitative approach with path analysis, involving 100 respondents selected by accidental sampling. The results of the analysis show that Electronic Word of Mouth and Traditional Word of Mouth have a significant effect on visitor satisfaction and visiting decisions. In addition, visitor satisfaction acts as a mediator that strengthens the relationship between the two types of WOM and the decision to visit. This research concludes that positive experiences shared through E-WOM and traditional WOM can increase satisfaction and encourage repeat visits. Suggestions for tourist destination managers are to actively utilize social media and improve service quality to increase visitor satisfaction. Local governments are also expected to support the development of facilities that enhance the visitor experience. Travelers are encouraged to share their experiences to help other potential visitors make better decisions. Keywords: E-WOM, traditional WOM, customer satisfaction, visiting decisions